Estudio de prefactibilidad para la instalación de una planta procesadora de proteína en polvo a base de suero de leche y albúmina de huevo - Chambergo Becerra, Juan Jesus (2022)
In recent years there has been a progressive growth in the fitness market, a reflection of this is the increase in functional training centers and gyms throughout Peru. According to the newspaper Gestión, gym goers spend an average of S/ 1500,00 per quarter on nutritional supplements, so there is a great opportunity in this market niche (Condor, 2020). The present pre-feasibility project seeks to take advantage of egg albumin and whey, resources in abundance on the Peruvian coast, to produce a sports supplement with high protein content, which comes at a price of S / 230 per month. final consumer. In this way, we can target socioeconomic sectors A, B and C to meet their needs, as demonstrated in the market study carried out. The project carried out includes a research plan, a market study to know the profile of the final consumer, in which it was determined that there is sufficient demand. In addition, there is a chapter on plant location and it was determined that Lurín is the ideal location to establish the company. It encompasses a technical study of the production processes and all aspects related to it, which made it possible to ensure that the project is technologically viable, and ends with an economic and financial analysis where a positive NPV is obtained for both scenarios. All this confirmed that the project will be profitable and will also have a social impact, as can be seen in chapter VIII.